SYMBOLIC MEANING OF KESANDINGAN RITUAL IN PROBOLINGGO - Nurhadi, Nurhadi; Faisol, Faisol; Ibrahim, Faisal Mahmoud Adam (El-HARAKAH (TERAKREDITASI), 2021)
Kesandingan, one of the rituals in Probolinggo, East Java, is a cultural phenomenon that mingles with religious elements of society. It is something sacred and mystical that parents do when a toddler (an infant under three years old) experiences heat illness for days, tends to be fussy, cries a lot, and cannot sleep at night. This research aims to explain the process of symbolic communication of kesandingan ritual and to understand the symbolic meaning behind the ritual. It is a descriptive-qualitative study through observation, in-depth interviews, and documentation. The data analysis uses a qualitative-naturalistic technique. The result demonstrates that the symbolic communication process of kesandingan ritual in Mentor, Sumberasih, Probolinggo, comprises seven series: burning incense, wiping incense smoke on the child's face, giving the child holy water to drink, wiping the child with floral water, preparing food, making a wish on the child's bed, and distributing food. Meanwhile, the symbolic meaning of kesandingan ritual refers to divine, social and personal dimensions.Â Ritual kesandingan merupakan salah satu ritual masyarakat Probolinggo Jawa Timur yang sudah menjadi fenomena budaya yang berbaur dengan unsur religi masyarakat. Ritual kesandingan merupakan sesuatu yang sakral dan mistis yang dilakukan orang tua saat anak batita (bawah tiga tahun) mengalami sakit panas berhari-hari, rewel, kerap menangis dan tidak bisa tidur terutama malam hari. Tujuan penelitian ini untuk menjelaskan proses komunikasi simbolik ritual kesandingan dan memahami makna simbolik dibalik ritual tersebuat. Penelitian ini merupakan penelitian deskriptif-kualitatif, pengumpulan datanya melalui observasi, wawancara mendalam, dan dokumentasi. Sedangkan analisis datanya menggunakan teknik analisa data kualitatif-naturalistik. Sebagai hasilnya, diketahui bahwa proses komunikasi simbolik ritual kesandingan di desa Mentor Kecamatan Sumberasih Kabupaten Probolinggo meliputi tujuh rangkaian yaitu: membakar kemenyan, mengusap asap kemenyan ke wajah anak, memberi minuman kepada anak dengan air doa, mengusap wajah anak dengan air bunga, menyiapkan makanan, memanjatkan doa ditempat tidur anak, dan membagikan makanan. Sedangkan makna simbolik ritual kesandingan mencakup tiga dimensi, yaitu: dimensi ketuhanan, sosial, dan personal.